Synopsis: Assessing agricultural extension agent digital readiness in Rwanda - Davis, Kristin E.; Rosenbach, Gracie; Spielman, David J.; Makhija, Simrin; Mwangi, Lucy (International Food Policy Research Institute, 2024)
The fourth Strategic Plan for Agriculture Transformation (PSTA IV) of the Government of Rwanda emphasizes extension and advisory services (EAS) as a priority area (MINAGRI 2018). In support of PSTA IV, the Ministry of Agriculture and Animal Resources (MINAGRI) began enhancing extension and advisory services by introducing a Customized Agriculture Extension System (CAES) (MINAGRI 2020). The CAES calls for ICT-supported extension services, stating that “ICT can revolutionize agriculture in Rwanda” (MINAGRI 2020: 34). Despite an enabling policy environment and Rwanda’s embracing of the ICT revolution, extension services have not taken advantage of the potential of ICTs (MINAGRI 2020). This paper looks at capacities of agricultural extension staff and the readiness of Rwandan public and private extension staff to use ICTs in their work—to be digitally equipped. A phone survey of 500 agricultural extension agents (EAs) was conducted in February and March 2021 across all districts of Rwanda among EAs in the public, private, and nonprofit sectors in Rwanda. We examine their demographics, education, and work backgrounds. To assess the ‘digital readiness’ of EAs, we assess the impacts of various factors on an EA’s digital experience and their attitudes toward digital modernization.